Unit price approval-planting reinforcing works - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for unit price approval-planting reinforcing works of Brac University new campus project.